(untitled) (Филолошки студии, 2019)
By the end of 1960th in SFRY everyone are more sharply felt contradictions between freedom declared by the government and real type of authority. Art workers of ’leaden’ decade (as 1970th when in SFRY the mode has sharply become tougher subsequently have been named), aspiring to be released from press of dominating ideology, enter confrontation with authority. The theory and practice of a modernism become here one of ways of alternative attitude, expression of disagreement with the state cultural policy. The Slovene cultural situation of 1960–70th became the important link during the democratization of a public and cultural life of republic, in many respects having paved the way for splash of national consciousness during the next decade. The creative intelligentsia which important force were differently minded Slovene modernists, in many respects promoted the destruction of political system.